2011
DOI: 10.4155/fmc.11.152
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of 1-Deamino-8- D -Arginine Vasopressin Analogs on Human Breast Cancer Cells

Abstract: Preclinical evaluation of the anti-tumor activity of [V(4)Q(5)]dDAVP in animal models is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…AVP has been shown to induce a dose-dependent (from 1 nM) and time-persistent increase of tumor cell proliferation. V2 receptors are present in human breast cancer (47), cervical cancer (85), and lung cancer (95) cells and in corticotrophinomas, with V2Rs varying greatly, being lower in macroadenomas than in microadenomas (126). An abnormal truncated V2R was also detected in MCF-7 cells, although it appeared to be nonfunctional (87)(88)(89).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 99%
See 1 more Smart Citation
“…AVP has been shown to induce a dose-dependent (from 1 nM) and time-persistent increase of tumor cell proliferation. V2 receptors are present in human breast cancer (47), cervical cancer (85), and lung cancer (95) cells and in corticotrophinomas, with V2Rs varying greatly, being lower in macroadenomas than in microadenomas (126). An abnormal truncated V2R was also detected in MCF-7 cells, although it appeared to be nonfunctional (87)(88)(89).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 99%
“…The presence of all AVP receptor subtypes, but particularly V2R, has been reported in transformed epithelial cells (86,89). V2R is present in a wide panel of human tumor cell lines, including human breast cancer cells (47), cervical cancer (85), lung cancer (95), and in corticotrophinomas (126).…”
mentioning
confidence: 99%
“…Interestingly, DDAVP inhibited experimental lung metastasis of mammary tumor cells in a mouse model (Alonso et al, 1999). In human breast cancer cell lines, DDAVP exhibits moderate antiproliferative effects (Iannucci et al, 2011). Concerning studies on canines, Hermo et al, (2008 and carried out two clinical trials in bitches with MMT to test the efficacy of perioperative administration of DDAVP after mastectomy.…”
Section: Conventional Therapies and New Treatment Strategiesmentioning
confidence: 99%
“…Interestingly, in a mouse model of breast cancer, DDAVP inhibited lung colonization by neoplastic cells (24). Since then, a number of studies have shown that this peptide seems to have antimetastatic and antiproliferative effects, both in mouse models of breast cancer and in different breast cancer cell lines (25, 26). Furthermore, a veterinary clinical trial has demonstrated that the perioperative administration of DDAVP increases the disease free and overall survival time in surgically treated bitches with mammary cancer of various histological types (27).…”
Section: Introductionmentioning
confidence: 99%